Macroeconomics Determinants of Saudi Arabia's Inflation 2000-2016: Evidence and Analysis - Naseem, Sana (International Journal of Economics and Financial Issues, 2018)
This study deals with rising prices in Saudi Arabia from 2000 to 2016. Inflation in an open economy can be influenced by both domestic and global factors. The aim of the paper is to examine macroeconomics determinants of inflation in Saudi Arabia. The study has employed regression model, in which the dependent variable is inflation (CPI) and independent variables are money supply, fixed exchange rate against U.S dollar, oil prices, import value, export value and unemployment. Empirical result shown that Money supply, fixed exchange rate against U.S dollar, import value, export value, and oil prices have statistical significance with inflation in Saudi Arabia except unemployment that does not directly predict inflation rates in Saudi Arabia. It has been concluded that effect of domestic factors on Saudi inflation eroded over the last 13 years as Saudi inflation become more globalized. Keywords: Saudi Arabia, Inflation, Macroeconomics Determinants, global factors. JEL Classifications: E60, E51, E31, F31